2001
DOI: 10.1046/j.1365-2141.2001.02681.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo generation of human cytomegalovirus‐specific cytotoxic T cells by peptide‐pulsed dendritic cells

Abstract: Summary. Adoptive transfer of donor-derived human cytomegalovirus (HCMV)-specific T-cell clones can restore protective immunity after stem cell transplantation. Ex vivo induction of HCMV-specific T cells using HCMV-infected fibroblasts as stimulator cells confines this approach to HCMV-seropositive donors and requires the presence of infectious virus during the stimulation procedure. In this study, we describe a potential alternative strategy to generate HCMV-specific T cells ex vivo for adoptive immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 40 publications
0
41
2
Order By: Relevance
“…Peptide pulsing of DC proved highly efficient for the selective stimulation and expansion of peptide-specific CTL in eight out of nine donors with pre-existing CD8 + cells against the peptide. This is in contrast to the findings of Kleihauer et al (2001), who reported a variable success of expanding CMV-directed CD8 + T cells. The expanded CTL specifically lysed T2 target cells pulsed with the cognate peptide, as also shown by others (Solache et al, 1999;Kleihauer et al, 2001).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Peptide pulsing of DC proved highly efficient for the selective stimulation and expansion of peptide-specific CTL in eight out of nine donors with pre-existing CD8 + cells against the peptide. This is in contrast to the findings of Kleihauer et al (2001), who reported a variable success of expanding CMV-directed CD8 + T cells. The expanded CTL specifically lysed T2 target cells pulsed with the cognate peptide, as also shown by others (Solache et al, 1999;Kleihauer et al, 2001).…”
Section: Discussioncontrasting
confidence: 55%
“…This is in contrast to the findings of Kleihauer et al (2001), who reported a variable success of expanding CMV-directed CD8 + T cells. The expanded CTL specifically lysed T2 target cells pulsed with the cognate peptide, as also shown by others (Solache et al, 1999;Kleihauer et al, 2001). MHC class I tetramers can be used for the direct isolation of CMV-specific T cells from leukapheresis products.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, infusion of CMVspecific CD8 ϩ T cell clones to hemopoietic stem cell recipients resulted in the restoration of CMV-specific immunity (12,19). Various combinations of APC and CMV Ags have been developed for the generation of CMV-specific T cell responses including CMV-infected fibroblasts (20); CMV-infected MoDC (21,22); MoDC pulsed with pp65 peptides (23,24); MoDC pulsed with recombinant pp65 protein (25); adenovirus vector-infected MoDC (26); vaccinia virus vector-infected MoDC (27); LCL transfected with pp65 gene (28); and retrovirus vector-infected LCL (29). All of the methods described to date have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The results, however, do not necessarily preclude the possibility of priming naive T cells with CD40-B/pp65 cells. Kleihauer et al (23) showed that cytotoxic T cell lines were generated from CMV-seronegative donors only in 2 of 11 donors starting with 3 ϫ 10 6 PBMC, even after stimulating with pp65 peptidepulsed MoDC. Szmania et al (24) also reported that only 2 of 10 CTL lines were pp65 specific, when 2 ϫ 10 6 PBMC were stimulated with MoDC.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, with a small proportion of CMV-seronegative donors it has been possible to generate CMV-specific T cells by in vitro priming (45)(46)(47). However, we expect it to be very difficult to translate these observations into feasible clinical procedures, because the precursor frequency of naive CMV-specific CD8 ϩ T cells in CMV-seronegative individuals, estimated from general considerations on TCR diversity (48), is unlikely to be above 1 in 10 6 naive T cells.…”
Section: Cd8mentioning
confidence: 99%